The causal impact of mental health on tobacco and alcohol consumption: An instrumental variables approach - Francis Mitrou; Ha Trong Nguyen; Huong Thu Le; Stephen R. Zubrick (Global Labor Organization (GLO), 2023)
The reciprocal relationship between psychiatric and substance use disorders is well-known, yet it remains largely unknown whether mental health morbidity causally leads to addictive behaviours. This paper utilises a fixed effects instrumental variables model, which is identified by time-varying sources of plausibly exogenous variations in mental health, and a nationally representative panel dataset from Australia to present robust evidence on the causal impact of mental distress on cigarette smoking and alcohol drinking behaviours. We find that mental distress significantly increases the prevalence and intensity of either cigarette or alcohol consumption. Further analysis reveals that mental distress also substantially increases household monetary expenditures on either tobacco or alcohol. The impact is greater for lower educated individuals or children of smokers, and is slightly higher for males. Our findings highlight the importance of mental health screening and treatment programs, especially among lower educated individuals or children of smokers, to assist in the prevention of addictive activities.
Keywords: C26; I10; I12; I14; 330; Mental Health; Depression; Smoking; Drinking; Alcohol Addiction; Instrumental Variables